Estimating long-term global supply costs for low-carbon hydrogen. (15th November 2021) - Brändle, Gregor; Schönfisch, Max; Schulte, Simon
Abstract: This article presents a comprehensive approach for estimating the development of global production and supply costs of low-carbon hydrogen from renewable energy sources (onshore wind, offshore wind and solar photovoltaics) and natural gas (natural gas reforming with carbon capture and storage and natural gas pyrolysis) until 2050. The analysis also assesses the costs associated with the transportation of hydrogen by ship or pipeline. The combination of production and transportation costs yields a ranking of cost-optimal supply sources for individual countries. Estimation results suggest that natural gas reforming with carbon capture and storage will be the most cost-efficient low-carbon hydrogen production pathway in the medium term (2020–2030). Production of hydrogen from renewable energy sources could become competitive in the long run (2030–2050) if capital costs decrease significantly. Until 2050, minimum production costs for hydrogen from renewable energy sources could fall to $1.5/kg under central assumptions and to below $1/kg under optimistic assumptions in some regions. The cost-optimal long-term hydrogen supply depends on regional characteristics, such as renewable energy potentials and gas prices. Imports of hydrogen from renewable energy sources are cost-effective where domestic production potential is small and/or cost-intensive. Additionally, good import conditions exist for countries which are connected to prospective low-cost exporters via existing natural gas pipelines that can be retrofitted to transport hydrogen. Due to the high cost of seaborne transport, hydrogen trade will most likely develop regionally along pipeline networks. Highlights: Comprehensive assessment of future global low-carbon H2 production and supply costs. H2 from natural gas is more cost effective than from RES the medium-term (2030). H2 from RES is potentially cost competitive in the long-term (2050). H2 trade will most likely be pipeline-based and thus concentrated regionally. The optimal long-term H2 supply mix varies significantly between countries/regions.